Genetic determinants of pathogenicity of Escherichia coli isolated from children with acute diarrhea in Maputo, Mozambique - Jose Sumbana; Elisa Taviani; Alice Manjate; Bianca Paglietti; Antonella Santona; Mauro M Colombo (Journal of Infection in Developing Countries)
Introduction: Diarrheagenic Escherichia coli (DEC) represents one of the leading cause of diarrhoea in developing countries. In this study a molecular approach was applied for the detection of diarrheagenic Escherichia coli (DEC) circulating in Maputo, Mozambique. Methodology: All isolates were PCR tested for species-specific genes and for 11 molecular markers: stx1, stx2, eae, bfpA, lt, st, ipaH, aap, aggR CVD432 and daaE. Results: Of the 80 E. coli isolated, 74% were potential DEC: 21% EIEC, 19% EPEC, 15% EAEC, 13% ETEC, 5% DAEC and 1% hybrids. Conclusion: This study revealed the complexity of the etiology of diarrhea caused by pathogenic E. coli in Mozambique, and the risk of the emergence of new pathogenic variants due to the horizontal transmission of pathogenicity factors.